Isolasi dan Identifikasi Molekuler Bakteri Salmonella Asal Tempe Dage Berdasarkan Gen 16S rRNA - Mazidah Noer Inayah; Suci Indah Budiarti; Rahayu Wulan (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to isolate Salmonella from tempe dage, particularly products sold in traditional markets in the Banyumas region, Central Java, and to identify the isolates through molecular analysis of the 16S rRNA gene. Isolation of Salmonella from dage samples was conducted using culture-based methods on several types of selective media specific for Salmonella. Identification was performed through biochemical characterization using the API 20E system and molecular analysis based on PCR amplification of the 16S rRNA gene. The resulting 16S rRNA sequences were subsequently analyzed using the BLAST tool available on the NCBI platform, and phylogenetic relationships were reconstructed with MEGA X. The study successfully obtained one bacterial isolate (TD.1), exhibiting transparent colonies with black centers on SSA medium. Biochemical tests including catalase activity, sugar fermentation, H₂S production, and citrate utilization showed positive results. Further identification using the API 20E system confirmed that isolate TD.1 belonged to the genus Salmonella. Molecular analysis of the 16S rRNA gene identified isolate TD.1 as Salmonella enterica. In conclusion, isolate TD.1, recovered from tempe dage was identified as Salmonella enterica. The presence of Salmonella enterica in dage highlights a potential health risk and underscores the need for improved food hygiene in traditional markets.